Implementasi Pembangunan Berkelanjutan Dalam Sektor Pariwisata Di Indonesia (Studi Kasus: Pantai Kutang Desa Labuhan Kecamatan Brondong Kabupaten Lamongan) - sayuti royali (Prosiding ESEC, 2023)
This study aims to analyze the implementation of sustainable development in the tourism sector using the concept of sustainable tourism through a descriptive analysis approach using the case study method. The results showed nine programs that must be planned to support the development of sustainable tourism in Kutang Beach, including environmental conservation efforts, community empowerment, waste management, infrastructure improvement, tourism promotion, and the establishment of policies and regulations that support sustainable tourism. This research is expected to contribute to economic development and the welfare of local communities, as well as become a reference for local governments and academics in planning sustainable tourism in other tourist destinations.